Insights into the epidemic characteristics and evolutionary history of the novel porcine circovirus type 3 in southern China. Issue 2 (26th November 2017) - Fu, X.; Fang, B.; Ma, J.; Liu, Y.; Bu, D.; Zhou, P.; Wang, H.; Jia, K.; Zhang, G.
Summary: Porcine circovirus type 3 (PCV3) is a newly identified circovirus from swine in the USA, China and Poland. This novel circovirus has been associated with porcine dermatitis and nephropathy syndrome (PDNS), reproductive failure and multisystemic inflammation; moreover, PCV3 poses a potential threat to the swine industry. In this retrospective study, a phylogenetic analysis was conducted to address the epidemiology and evolutionary dynamics of this novel circovirus. The total positive sample rate of PCV3 was 26.7% (76/285) and has increased gradually over the past 3 years. Of these PCV3‐positive samples, 22.3% (17/76) were coinfected with PCV2. PCV3 can be detected in multiple sample types with different positive rates, and the positive rate is highest among stillborn. We also divide PCV3 into three clades (PCV3a, PCV3b and PCV3c) based on two amino acid mutations (A24V and R27K) on the cap protein in this study. In addition, the origin of PCV3 was approximately 1966 and may have originated from a bat‐associated circovirus. Our results suggested that PCV3 is widely distributed in southern China and has been circulating in swine herds for nearly half a century. PCV3 has evolved into different clades caused by mutations in cap proteins; thus, further research on PCV3 epidemiology should be conducted.